The lysosomal trafficking regulator “LYST”: an 80-year traffic jam - Turner, Mackenzie E.; Che, Jingru; Mirhaidari, Gabriel J. M.; Kennedy, Catherine C.; Blum, Kevin M.; Rajesh, Sahana; Zbinden, Jacob C.; Breuer, Christopher K.; Best, Cameron A.; Barker, Jenny C. (Frontiers in Immunology, 2024)
Lysosomes and lysosome related organelles (LROs) are dynamic organelles at the intersection of various pathways involved in maintaining cellular hemostasis and regulating cellular functions. Vesicle trafficking of lysosomes and LROs are critical to maintain their functions. The lysosomal trafficking regulator (LYST) is an elusive protein important for the regulation of membrane dynamics and intracellular trafficking of lysosomes and LROs. Mutations to the LYST gene result in Chédiak-Higashi syndrome, an autosomal recessive immunodeficiency characterized by defective granule exocytosis, cytotoxicity, etc. Despite eight decades passing since its initial discovery, a comprehensive understanding of LYST's function in cellular biology remains unresolved. Accumulating evidence suggests that dysregulation of LYST function also manifests in other disease states. Here, we review the available literature to consolidate available scientific endeavors in relation to LYST and discuss its relevance for immunomodulatory therapies, regenerative medicine and cancer applications.The Lysosomal Trafficking Regulator (LYST): The RoadmapIn 1943, a pediatrician discovered a strange, previously uncharacterized disease. The pediatrician described the patients' peripheral blood smears as containing abnormally large, distended granules, a first-in-man observation (1,2). Clinicians in Cuba and Japan corroborated these findings, reporting similar childhood cases unified by three hallmark features: oculocutaneous albinism, granule abnormality, and death in early childhood (3,4). This disease came to be known as Chédiak-Higashi